Militaria w pismach Łukasza Górnickiego - Bołdyrew, Aleksander (Acta Universitatis Lodziensis. Folia Historica, 2008)
This study deals with military accessories in XVIth century Poland in the light of historiographical relations, that is things and matters connected with an army, military services (an emphasis was put on accessories used by a soldier). The study is based on two works by L. Górnicki Dworzanin polski and Dzieje w Koronie Polskiej. Ł. Górnicki (1527-1603) was a courtier of bishops S. Maciejowski and A. Zebrzydowski, an envoy to Vienna and even a secretary of king Sigismund 11 August. Weapon knowledge systematics was preserved in the work, that is a division into offensive and defensive weapon and military equipment. Among offensive weapon L. Górnicki mentioned sabres which became more and more popular in XVIth century in Poland. It is worth mentioning that both swords and knives producers were applying for the right to produce the sabres. Another offensive weapon was a "hauswehre” - sword numbered by the contemporary of those days, just like a sabre, among fighting knives. This kind of weapon was cheap and easily available. Ł. Górnicki described an unfortunate accident which took place during a shooting show and in the time of Sigismund II August s visit at Prussian duke’s. In this description the author mentioned a sephelin. It was as a short spear with a big spearhead and spearshaft bound with leather bands. There is also a remark on trench mortars and problems faced by gunner who obviously did not know parabolic theory of bullet lead. Górnicki described also several tournaments organized at the king's court, for instance the one in 1533 or in 1539. It is possible to find not only descriptions of tournament customs (e.g. hasliludium hussaronicum) but also armament, mainly protective. Górnicki also noticed personal participation of Sigismund II August in knights’ struggles and he described fighting horses, which mirrors the role of horses in life of noblemen especially an army in Renaissance Poland. It was emphasized that people risked their life to capture horses which was frequently criticized but not abandoned. Ł. Górnicki’s account can be highly valued especially that he himself was for many years a courtier and a secretary of Sigismund II August so he knew the described reality very well. Historiographical sources – in contrast to economic sources – remark not only on the object itself but they also place it in a cultural context, which expands our knowledge of material culture history and historical weapon knowledge.